2007
DOI: 10.1007/s00018-007-7020-3
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic potentials of the human polyomavirus regulatory proteins

Abstract: The polyomaviruses BK, JC and SV40 are common in the human population. Their DNA genomes encode large T-antigen, small t-antigen, agnoprotein, and the capsid proteins VP1-3. Studies with these viruses have contributed extensively to the understanding of processes such as replication, transcriptional and posttranscriptional regulation, and cell cycle control. All three viruses can transform human cells in vitro, can induce tumours in animal models, and are strongly association with certain human cancers. It is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
87
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(89 citation statements)
references
References 215 publications
(202 reference statements)
1
87
0
1
Order By: Relevance
“…The strong affinity of Tag for binding and inactivating p53 results in the cell avoiding key cell cycle checkpoints, thus surviving the otherwise fatal DNA damage and undergoing mitosis. 24,25 By escaping apoptosis and surviving, asbestos-damaged SV40 infected mesothelial cells pave the way to malignant transformation. It is very likely that asbestos fibres and viral Tag and tag interact and synergistically activate cellular signalling pathways, especially the ERK/ AP-1 pathway, that lead to cell proliferation, malignant transformation and invasion.…”
Section: Asbestos and Sv40 Co-carcinogenitymentioning
confidence: 99%
“…The strong affinity of Tag for binding and inactivating p53 results in the cell avoiding key cell cycle checkpoints, thus surviving the otherwise fatal DNA damage and undergoing mitosis. 24,25 By escaping apoptosis and surviving, asbestos-damaged SV40 infected mesothelial cells pave the way to malignant transformation. It is very likely that asbestos fibres and viral Tag and tag interact and synergistically activate cellular signalling pathways, especially the ERK/ AP-1 pathway, that lead to cell proliferation, malignant transformation and invasion.…”
Section: Asbestos and Sv40 Co-carcinogenitymentioning
confidence: 99%
“…2 The aforementioned viruses BKV, JCV and SV40, or their early proteins can induce tumors in animal models, and can immortalize or transform cultured cells, including human cells. 4,12 However, similar studies on the newly discovered polyoma viruses are lacking.…”
Section: Dear Editormentioning
confidence: 99%
“…Recently, the interplay of the microenvironment, pathogens, immunity, inflammation, cellular epigenetic alterations and various chronic diseases has attracted increasing attention. [12][13][14] Previous studies thus far have shown that factors, such as disease stage, clinical parameters and methodological issues are rather minor issues. It is becoming more evident that further studies are required to determine whether polyomavirus may be placed among the determinants of risk.…”
Section: Dear Editormentioning
confidence: 99%
“…The early proteins have regulatory functions, and a small number of mammalian PyVs have been reported to be tumorigenic in their natural host. Although 13 distinct human polyomaviruses have at present been discovered and the oncogenic properties of the human BK polyomavirus (BKPyV), JC polyomavirus (JCPyV) and the Merkel cell polyomavirus (MCPyV) in vitro and in animal models have been documented by numerous reports (reviewed in [2][3][4][5]), MCPyV is presently the only human virus that seems to be associated with human cancer (Merkel cell carcinoma, MCC) [6] (reviewed in [7]). BKPyV and JCPyV have also been linked to cancer development but this issue remains controversial and largely unresolved (reviewed in [8][9][10][11]).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, murine PyV (MPyV) [16,17], hamster PyV (HaPyV) [18] and simian virus 40 (SV40) [19] induce tumours in laboratory animals under experimental conditions. Large T antigen (LTAg) and small T antigen (STAg) are known to play an essential role in viral transcription and replication [2,[20][21][22]. LTAg drives the infected cell into S phase status, the condition for optimal viral replication, and recruits cellular replication factors for promoting viral DNA replication via its helicase domain [22,23].…”
Section: Introductionmentioning
confidence: 99%